(untitled) (Research, Society and Development, 2022)
This study aims to validate the content of the qualitative research instrument on bilingualism in international schools, using the Content Validity Coefficient method used by Hernández-Nieto (2002). Given the restrictions due to existing copyrights mainly in educational franchises, this questionnaire constitutes a source for studies on the internationalization of studies in basic education through the curriculum and methodology of international schools in Brazil. The methodology presents Delphi rounds and application of the Content Validity Coefficient to evaluate the questions and the judges. The questions that make up the questionnaire were evaluated in the questions clarity and pertinence to the theme studied by five specialist professors with master’s and doctorate degrees in education working in basic education in international schools. The results show that the questions obtained a score higher than 0.8 in the two categories analyzed and index per judge free of error of 0.96, confirming the clarity and relevance of the research instrument.